Identification of quorum sensing-regulated Vibrio fortis as potential pathogenic bacteria for coral bleaching and the effects on the microbial shift - Sun, Xiaohui; Li, Yan; Yang, Qian; Zhang, Han; Xu, Nuo; Tang, Zheng; Wu, Shishi; Jiang, Yusheng; Mohamed, Hala F.; Ou, Danyun; Zheng, Xinqing (Frontiers in Microbiology, 2023)
Coastal pollution, global warming, ocean acidification and other reasons lead to the imbalance of coral reef ecosystem, resulting in the increasingly serious problem of coral degradation. Coral bleaching is often accompanied by structural abnormalities of coral symbiotic microbiota, among which Vibrio is highly concerned. In this study, Vibrio fortis S10-1 (MCCC 1h00104) isolated from sea cucumber, was used for the bacterial infection on coral Seriatopora guttatus and Pocillopora damicornis. The infection of S10-1 led to the coral bleaching and significant reduction of photosynthetic function in coral holobiont, and the pathogenicity of V. fortis was regulated by quorum sensing. Meanwhile, Vibrio infection also caused shift of coral symbiotic microbial community, with significant increased abundant Proteobacteria and Actinobacteria and significant reduced abundant Firmicutes; on genus level, the abundance of Bacillus decreased significantly, and the abundance of Rhodococcus, Ralstonia and Burkholderia-caballeronia-paraburkholderia increased significantly; S10-1 infection also significantly impacted on the water quality in the micro-ecosystem. On the other hand, S10-1 infection showed less effect on the microbial community in the live stone, which reflected that the microbes in the epiphytic environment of the live stone might have stronger ability of self-regulation; the symbiotic zooxanthellae were mainly consisted of Cladocopium sp. and showed no significant effect by the Vibrio infection. This study verified that V. fortis is the primary pathogenic bacterium causing coral bleaching, revealed the changes of microbial community caused by its infection, provided a strong evidence for the "bacterial bleaching" hypothesis, and provided experimental experience for the exploration of the interaction mechanism among microbial communities, especially coral-associated Vibrio in coral ecosystem.